Ethics of vaccine refusal - Kowalik, Michael (Journal of medical ethics, 2022)
Proponents of vaccine mandates typically claim that everyone who can be vaccinated has a moral or ethical obligation to do so for the sake of those who cannot be vaccinated, or in the interest of public health. I evaluate several previously undertheorised premises implicit to the ‘obligation to vaccinate’ type of arguments and show that the general conclusion is false: there is neither a moral obligation to vaccinate nor a sound ethical basis to mandate vaccination under any circumstances, even for hypothetical vaccines that are medically risk-free. Agent autonomy with respect to self-constitution has absolute normative priority over reduction or elimination of the associated risks to life. In practical terms, mandatory vaccination amounts to discrimination against healthy, innate biological characteristics, which goes against the established ethical norms and is also defeasible a priori.